2022
DOI: 10.1055/s-0042-1748971
|View full text |Cite
|
Sign up to set email alerts
|

Patient Acceptance of Telemedicine in Urogynecology Consultations – A Cross-Sectional Study Performed at a Brazilian Public Institution

Abstract: Objective To evaluate the acceptance of telemedicine and determine its associated factors in an urogynecology outpatient clinic of a public hospital in Brazil. Methods The present was a cross-sectional study performed between June and November 2020. The included patients had their elective appointments postponed due to the coronavirus disease 2019 (COVID-19) pandemic. The variables considered regarding the acceptance of telemedicine were: urogynecologic diagnosis, age, level of schooling, place of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…In summary, telemedicine acceptance in our study was high and comparable to other investigations that have examined acceptance in other collectives: for example, 1 study in patients who were urogynecologic found 87% acceptance [ 35 ], while 2 scoping reviews found high acceptance of telemedicine in palliative care [ 36 ] and older adult patients with tumors [ 37 ]. In another cross-sectional study of patients with tumors, high satisfaction was found, with a mean of 5.5 out of 7 [ 38 ].…”
Section: Discussionsupporting
confidence: 88%
“…In summary, telemedicine acceptance in our study was high and comparable to other investigations that have examined acceptance in other collectives: for example, 1 study in patients who were urogynecologic found 87% acceptance [ 35 ], while 2 scoping reviews found high acceptance of telemedicine in palliative care [ 36 ] and older adult patients with tumors [ 37 ]. In another cross-sectional study of patients with tumors, high satisfaction was found, with a mean of 5.5 out of 7 [ 38 ].…”
Section: Discussionsupporting
confidence: 88%